Surgery for abdominal aortic aneurysms Results of the last 10 years in the Hospital de Clínicas - Kamaid Toth, Emil; Dutto, Gabriel; Esperón, Alejandro; López Chapuis, Daniel; Piaggio, José (Cirugía del Uruguay, 2001)
The review has de purpose of establishing the frequency and results of abdominal aortic aneurysm (AAA) surgery in the Hospital de Clínicas (University Hospital) of Montevideo, and covered data of patients operated from January 1988 through Ju/y 1998